Academic Misconduct in Higher Education - Al-Sarraf, Mrs. Hanan Hassan (Arab Journal for Sciences and Research Publishing, 2017)
This paper discussed the academic misconduct upon previous research papers. A descriptive deign used to collect data from studies done in regions all over the world, including Europe, East Asia, and Sub-Saharan Africa. Prevalence of academic misconduct and how students engage in misconduct in universities and colleges, and strategies to overcome academic misconduct were discussed. In the future direction section, an emphasis is made on the unique challenge academic misconduct presents in the online environment. Lastly, its recommended to apply multi-faceted approach in addressing academic misconduct since no single strategy has been found to be effective.